Pengembangan Media Pembelajaran Sains Berbasis Prezi untuk Siswa Sekolah Dasar pada Materi Penggolongan Hewan - Muharni Muharni; Mahmud Alpusari; Zetra Hainul Putra (Journal of Natural Science and Integration, 2021)
This study aims to design and develop Prezi based learning media on animal classification topic. The method used is research and development based on ADDIE model, including analysis, design, develop, implementation, and evaluation. Data were collected through questionnaires. After analyzing curriculum and design Prezi based learning media on animal classification, the research continued into the developmental process. In this step, the media were validated by three experts, namely language, media, and content experts. The results showed Prezi based learning media on animal classification has high validation criteria to be used in learning science in elementary school. Then, Prezi based learning media was tested with 21 third grade students from a private school in Pekanbaru. The results shows that Prezi based learning media have effective in supporting students to learn animal classification, and the students were very motivating and enjoy learning. The implication of this study is that there is high potential for using Prezi based learning media in learning science. Keywords: animal classification, development research,  Prezi-based learning.ABSTRAKPenelitian ini bertujuan untuk merancang dan mengembangkan media pembelajaran berbasis Prezi pada topik klasifikasi hewan. Metode yang digunakan adalah penelitian dan pengembangan berdasarkan model ADDIE, meliputi analisis, perancangan, pengembangan, implementasi, dan evaluasi. Data dikumpulkan melalui kuesioner. Setelah menganalisis kurikulum dan merancang media pembelajaran berbasis Prezi pada klasifikasi hewan, penelitian dilanjutkan ke proses pengembangan. Pada tahap ini media divalidasi oleh tiga orang ahli yaitu ahli bahasa, ahli media, dan ahli isi. Hasil penelitian menunjukkan media pembelajaran berbasis Prezi klasifikasi hewan memiliki kriteria validasi tinggi untuk digunakan dalam pembelajaran IPA di sekolah dasar. Kemudian media pembelajaran berbasis Prezi diujicobakan kepada 21 siswa kelas III sekolah swasta di Pekanbaru. Hasil penelitian menunjukkan bahwa media pembelajaran berbasis Prezi efektif dalam mendukung siswa dalam belajar klasifikasi hewan, dan siswa sangat memotivasi serta menikmati pembelajaran. Implikasi dari penelitian ini adalah tingginya potensi penggunaan media pembelajaran berbasis Prezi dalam pembelajaran IPA.Kata kunci: penelitian pengembangan, pembelajaran berbasis Prezi.